Trimming a high-fidelity multibody helicopter model for performance and control analysis - Trainelli, L.; Croce, A.; Riboldi, C.E.; Possamai, R. (My University, 2015)
This paper brings forward the study of the dynamic behaviour of a novel lightweight helicopter featuring an innovative gimballed two-bladed main rotor. First, previous results for the isolated main rotor are extended for the case of free-coning under cyclic pitch perturbations and longitudinal gusts. Subsequently, the complete helicopter is modelled and a simple control system is derived and applied to steer the helicopter to steady hover and straight flight conditions, showing good characteristics also under gust perturbations.
Keywords: Flight Mechanics